Analysis of the Communication Strategy of the Head of Business Development in Improving Service Quality for Customers Case Study of PT Catur Prima Perkasa - Sihaloho, Rudi; Yulianto, Yulianto; Astuti, Marhanani Tri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research analyzes the communication strategies that can be used by the Head of Business Development to improve service quality at PT Catur Prima Perkasa, a distributor of iron pipes, valves, and fittings in Indonesia. The background of this research is based on the company's need to understand and improve service quality for customers. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews and analysis of related documents. Data analysis techniques were conducted using Content Analysis, and data validity testing through triangulation. The results showed that the combination of various communication methods can identify patterns and obstacles in delivering messages, and provide insight for companies in improving services. In conclusion, the implementation of the right communication strategy can improve service quality for customers at PT Catur Prima Perkasa.